Multivariate Analysis of Finnish Dialect Data—An Overview of Lexical Variation. - Hyvönen, Saara; Leino, Antti; Salmenkivi, Marko (Literary & Linguistic Computing, 2007)
During the process of writing a comprehensive dictionary of Finnish dialects, a large set of maps describing the regional distribution of the dialect words have been compiled in electronic form. In this article, we set out to analyse this corpus of data in order to gain new insight on the variation of Finnish dialects. We use a wide range of multivariate data analysis methods, including principal components analysis, independent components analysis, clustering, and multi-dimensional scaling. We explain how to preprocess the data to overcome the problem of uneven sampling caused by the way the data has been collected. We discuss the results obtained by these methods and compare them to the traditional view of Finnish dialect groups.